การพัฒนาแนวทางในการกำกับคุณภาพการให้บริการก๊าซธรรมชาติสำหรับอุตสาหกรรม - วุฒิภูมิ ศรีวิชา (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To develop key performance indicators (KPIs) suitable for practicing and reflecting natural gas service quality for industrial sectors of the studied company. It also includes the existing controlling and evaluating indices of the studied company to be synchronized with the company’s goals. The research starts with studying and collecting all related KPIs of both studied company and comparable global practices, which leads to the next step to categorize them to four aspects based on EU’s concept; i.e., quality, continuity, reliability, and customer satisfaction. As a result of the benchmarking, the 83 indicators are selected and obtained to derive questionnaire used for respresenting the director’s opinions and refining indicators specialized for each aspect fallen within 2 main criteria, which are consistency of the organization and readiness of the data. The analytic network process (ANP) is then employed to prioritize and support robust multicriteria decision-making, which is compiled by Super Decisions 2.0.8 resulting 28 indicators covering four aspects as stated earlier. These indicators are then used for seeking the opinions from the directiors of the companies. In addition, sampling assessments are conducted on one power plant and one manufacture. Having gone through these processes, the indicators are systematically amended. Finally, both wholesale distributor license and retail distributor license have 10 similar KPIs which are applicable and acceptable in views of all related parties.